What Motivates Different People to Participate in Game Jams? - de Almeida Melo, Leandro; H. S. Leite, Tiago; Freire, Fábio; G. Perin, Marcelo; Figueira Filho, Fernando; R. B. de Souza, Cleidson; D. Batista, Any Caroliny (Anais Estendidos do Simpósio Brasileiro de Sistemas Colaborativos (SBSC); 2019: Anais Estendidos do XV Simpósio Brasileiro de Sistemas Colaborativos, 2019)
Game jams have been attracting an increasingly diverse audience, with thousands of participants getting together to build game prototypes every year. However, little is understood about these people's motivations to participate in such events and how their motivations differ according to their type of involvement with game development. Through a large-scale survey with attendees of a global-scale game jam, we found that indie developers are the ones most influenced by social motivations, while students and hobbyists favor the opportunity to strengthen technical skills more than other groups. Our findings provide a better understanding of the motivations for participating in game jams by studying these motivations across different groups of participants.